Agency costs and organizational architecture of large corporate farms: evidence from Brazil - Fabio Chaddad; Vladislav Valentinov (International Food and Agribusiness Management Review, 2017)
Drawing inspiration from American institutionalism and new institutional economics, this paper discusses the rise of large corporate farms as the transition from the classic capitalist firm to the corporate form of organization based on the separation of ownership and control. Three case studies from the Brazilian cerrado show the rise of large corporate farms to be enabled and impelled by the advance of agricultural production technologies and the search for scale economies. The key finding from the case studies is that complex technology not only necessitates large-scale farming but also generates technical and organizational solutions to the potentially pervasive agency problems. In addition to the use of sound corporate governance practices, these solutions include organizational architecture encompassing computer-aided accounting and budgeting systems, incentive-based compensation, clear definition of performance goals, and delegation of operational decisions to farm managers. Furthermore, organizational architecture has been shown to promote a culture of trust and accountability, which counteract the opportunistic tendencies of farm managers and workers.
Keywords: D23; L22; Q13; 330; corporate farms; separation of ownership and control; organizational architecture; corporate governance